The SMART scheduler: a revolutionary scheduling system for secondary schools - Muggy, Timothy Luke (Kansas State University, 2011)
Westside High School (WHS) of Omaha, Nebraska utilizes a novel scheduling system called Modular scheduling. This system offers numerous advantages over the standard school day in terms of student learning and faculty development. Modular Scheduling allows teachers to design the structure of their own classes by adjusting the frequency, duration and location of each of their daily lessons. Additionally, teachers are able combine their classes with those of other teachers and team-teach. Modular scheduling also allows for open periods in both students’ and teachers’ schedules. During this time, students are able to complete school work or seek supplemental instruction with a teacher who is also free. Teachers are able to use their open mods to plan, meet in teams and help students who have fallen behind. Currently, a semester’s class schedules are constructed over the course of a seven week period by a full-time employee using a computer program developed in FORTRAN®. The process is extremely tedious and labor intensive which has led to considerable wasted time, cost and frustration. This thesis presents a novel scheduling program called the SMART Scheduler that is able to do in seconds what previously took weeks to accomplish. Once parameters have been input, The SMART Scheduler is able to create cohesive class schedules within a modular environment in less than 6 seconds. The research presented describes the steps that were taken in developing the SMART Scheduler as well as computational results of its implementation using actual data provided by WHS. The goal of this research is to enable WHS and other schools to efficiently and effectively utilize modular scheduling to positively affect student learning.
Keywords: Class Scheduling; Schedules; Scheduling; Operations Research; Operations Research (0796)